Site-specific nutrient management in rice (Oryza sativa): Status and prospect–A review - L K BAISHYA; SHIVA DHAR MISHRA; TEEKAM SINGH (The Indian Journal of Agricultural Sciences, 2022)
Site-specific nutrient management (SSNM) plays a vital role in increasing crop profitability, maintaining soil health and reducing environmental pollution. Field experiments and demonstrations conducted across southeast (SE) Asia were conducted during 2020-21 at ICAR-Indian Agricultural Research Institute, New Delhi and observed that SSNM includes various nutrient management practices and each practice have a positive impact on fulfilling its vital role. After a thorough study, this review reflects that fertilizer recommendations based on targeted yield concept were more balanced, profitable and helpful in controlling soil nutrient mining and essential for sustainable crop production. Establishment of an attainable yield target, based on location, season, climate, rice cultivar and crop management ensures effective use of existing indigenous nutrients such as from soil, organic amendments, crop residue, manure and irrigation water and application of fertilizer to dynamically fill the deficit between crop needs and indigenous supply and to maintain soil fertility. Moreover, use of nitrification inhibitor, deep placement of nitrogen (N) and NPK fertilizers reduces the loss of N fertilizers up to 20% and increases rice yield up to 10%. The leaf colour charts (LCC), chlorophyll meter or SPAD are inexpensive need based tools for fertilizer N management that can reduce the excessive application of N (10-50%). Optical sensor-based nitrogen management is an alternative to LCC and SPAD that can quickly and reliably monitor N requirements of rice. On the other hand, the dissemination of SSNM through LCC, SPAD, QUEFT models, optical sensor etc., requires training of researchers, local extension workers, fertilizer retailers, and farmer leaders on techniques and guidelines for enabling rice farmers. Therefore, a simple nutrient decision support tool, Nutrient Expert® (NE) is useful to develop strategies to manage fertilizer N, P and K tailored to farmer's field or growing environment. However, comparative evaluation of different SSNM approach is essential for location wise fertilizer prescription for increasing crop profitability, soil health and environmental safety.